School Culture and Its Role in Shaping Students”™ Religious Attitudes: A Case Study at SMA Nurul Islam Bekasi - Puadah, Popi; S, R.Kukun Agung; Rosyada, Dede; Harun, Hanifah Musa Fathullah (Universitas Muhammadiyah Magelang, 2025)
This study aims to examine the role of school culture in shaping students”™ religious attitudes at SMA Nurul Islam Bekasi. A qualitative approach with a case study design was employed. Data were collected through classroom and school observations, in-depth interviews with teachers, students, and school staff, as well as document analysis of school policies and religious programs. The data were analyzed using NVivo software to identify emerging themes and patterns. The findings reveal that school culture plays a significant role in fostering students”™ religious attitudes through the internalization of religious routines, teacher role modeling, religiously grounded social interactions, and a supportive school environment. These cultural elements contribute to the holistic development of students”™ religious attitudes, encompassing cognitive, affective, and behavioral dimensions. The study highlights that the formation of students”™ religious attitudes is not solely determined by formal religious instruction, but is strongly influenced by a consistently cultivated and sustainable school culture. The findings offer practical implications for schools in strengthening character education through the development of a religious school culture.